Co-inoculation of native multi-trait plant growth promoting rhizobacteria promotes plant growth and suppresses Alternaria blight disease in castor (Ricinus communis L.). Issue 12 (December 2022) - Sandilya, Sosanka Protim; Jeevan, B.; Subrahmanyam, Gangavarapu; Dutta, Kironta; Vijay, N.; Bhattacharyya, Nabanita; Chutia, Mahananda
Abstract: Background: Castor ( Ricinus communis L.) is cultivated for seed oil and to feed (leaves) Eri silkworm, Samia ricini (Donovan) Hutt. Alternaria blight affects castor cultivation resulting substantial yield loss (∼30%). Uses of synthetic fertilizers and agrochemicals for disease management have serious concerns as the castor leaves are fed to eri silkworms for rearing. Application of plant growth promoting rhizobacteria for disease suppression and to enhance plant growth will be a healthier choice in castor cultivation. The aim of this study was to assess the efficacy of Alternaria blight disease suppression by native rhizobacteria isolated from wasteland castor and their ability on plant growth promotion. Methodology: We isolated 50 bacterial antagonists from castor rhizosphere using the dilution plate method and evaluated their antagonistic activity against the castor blight pathogen, Alternaria ricini . Based on antimicrobial bioassay and plant growth promotion (PGP) traits (phosphate solubilization, ACC deaminase activities, production of IAA, GA3, HCN, NH3 and siderophore), salt and acid tolerance; we have chosen ten potential isolates and identified them through 16SrRNA gene sequencing and analysis. Disease suppression and plant growth studies were evaluated in pot experiments. Results and conclusion: Three isolates namely, Enterobacter hormaechei (LRP-2), Bacillus mycoides (HF-1) and B. aryabhattai (UR-6) showed potential antagonistic activities and PGP traits which were selected for disease suppression and PGP studies. Application of PGPR consortia (LRP-2+HF-1) could suppress the plants from A. ricini infection in challenged inoculation. Mix inoculation of LRP-2 and UR-6 showed synergistic effect and enhanced plant growth in pot experiments. Combinations of E. hormaechei (LRP-2), B. mycoides (HF-1) and B. aryabhattai (UR-6) can be applied as bio-control and bio-fertilizer formulation to protect castor from Alternaria blight and also to enhance plant growth. Highlights: We isolated native rhizobacteria of castor growing in cultivated and wastelands. Ten PGPR were selected for disease suppression and plant growth experiments. Inoculation of native PGPR could suppress Alternaria blight disease in Castor. Co-inoculation of PGPR strains also enhanced plant growth and biomass. Abstract : Castor; Alternaria blight; antagonists; Plant growth promoting rhizobacteria (PGPR); wasteland.